(untitled) (Research, Society and Development, 2024)
Objetives: Map the known evidence to characterize the instruments used to assess nursing workload of family nurses. Methods: Scoping review, guided by the methodology proposed by the Joanna Briggs Institute for conducting scoping reviews, consisting of 3 research stages: 1) initial research in Medline and CINHAL; 2) extended search, using keywords and search terms, in the following databases: JBI, CINAHL Complete, MEDLINE, Cochrane and Scopus; 3) Search the references of selected articles. No time limit is defined. Results: With this scoping review we intend to present a broad mapping of studies that use instruments to evaluate family nurse’s workload. Conclusion: Mapping the available evidence on the instruments used to assess the workload of family nurses, will contribute to the dissemination of available evidence on the topic and will allow for the identification of gaps in the literature.